Interleukin 17-A inhibition in the treatment of psoriasis. (2nd January 2016) - Yiu, Zenas ZN; Griffiths, Christopher EM
Abstract : Interleukin (IL) 17-A appears to be integral to the pathogenesis of chronic plaque psoriasis. Recent clinical trials have shown that blockade of this cytokine with the biologic therapies—secukinumab, ixekizumab and brodalumab—have led to unprecedented treatment efficacy for psoriasis. In addition, their dual efficacy towards psoriatic arthritis increases their potential clinical utility and they promise to be an important treatment option for patients who have tumour necrosis factor inhibitor resistant disease. Here, we present the evidence for the high treatment efficacy of the IL-17A inhibitors but also discuss some potential questions and areas of research needed, including the lack of evidence behind the drug survival, immunogenicity and safety profile.